Aligning in-plane polarization multiplies piezoresponse in P(VDF-TrFE) films on graphite. (31st October 2018) - Roth, Robert; Koch, Martin; Schaab, Jakob; Lilienblum, Martin; Syrowatka, Frank; Band, Tino; Thurn-Albrecht, Thomas; Dörr, Kathrin
Abstract: Ferroelectric polymers are promising as piezoelectric sensors and devices for data storage, energy harvesting and fast energy storage. However, efficient electric polarization as well as piezoelectric and dielectric responses of as-deposited films are often much lower than expected in a crystalline model, because the local orientations of electric dipoles show substantial disorder. Here we introduce an approach for in-plane alignment of the polarization based on applying soft mechanical pressure with a force microscopy tip. Micron-sized ferroelectric domains with well-defined in-plane and out-of-plane polarization orientation and low surface roughness have been written in poly(vinylidene fluoride-trifluoroethylene) (PVDF-TrFE) films on graphite. Inside such domains, the piezoelectric response is more than four times that of the untreated film. The achieved polarization alignment can advance the performance of many devices, since it reduces the cancellation of local responses to electric fields or mechanical strains resulting from polarization disorder.